Valley Manipulation by Optically Tuning the Magnetic Proximity Effect in WSe2/CrI3 Heterostructures - Seyler, Kyle L; Zhong, Ding; Huang, Bevin; Linpeng, Xiayu; Wilson, Nathan P; Taniguchi, Takashi; Watanabe, Kenji; Yao, Wang; Xiao, Di; McGuire, Michael A; Fu, Kai-Mei C; Xu, Xiaodong (Nano letters, 2018)
Monolayer valley semiconductors, such as tungsten diselenide (WSe2), possess valley pseudospin degrees of freedom that are optically addressable but degenerate in energy. Lifting the energy degeneracy by breaking time-reversal symmetry is vital for valley manipulation. This has been realized by directly applying magnetic fields or via pseudomagnetic fields generated by intense circularly polarized optical pulses. However, sweeping large magnetic fields is impractical for devices, and the pseudomagnetic fields are only effective in the presence of ultrafast laser pulses. The recent rise of two-dimensional (2D) magnets unlocks new approaches to controlling valley physics via van der Waals heterostructure engineering. Here, we demonstrate the wide continuous tuning of the valley polarization and valley Zeeman splitting with small changes in the laser-excitation power in heterostructures formed by monolayer WSe2 and 2D magnetic chromium triiodide (CrI3). The valley manipulation is realized via the optical control of the CrI3 magnetization, which tunes the magnetic exchange field over a range of 20 T. Our results reveal a convenient new path toward the optical control of valley pseudospins and van der Waals magnetic heterostructures.